“Do animals have accents?”: talking with agents in multi-party conversation - Porcheron, Martin; Fischer, Joel E.; Sharples, Sarah (2016)
In this paper we unpack the use of conversational agents, or so-called intelligent personal assistants (IPAs), in multi- party conversation amongst a group of friends while they are socialising in a café. IPAs such as Siri or Google Now can be found on a large proportion of personal smartphones and tablets, and are promoted as ‘natural language’ interfaces. The question we pursue here is how they are actually drawn upon in conversational practice? In our work we examine the use of these IPAs in a mundane and common-place setting and employ an ethnomethodological perspective to draw out the character of the IPA-use in conversation. Additionally, we highlight a number of nuanced practicalities of their use in multi-party settings. By providing a depiction of the nature and methodical practice of their use, we are able to contribute our findings to the design of IPAs.